Differential Transcriptomic Regulation in Sweet Orange Fruit (Citrus sinensis L. Osbeck) Following Dehydration and Rehydration Conditions Leading to Peel Damage - Romero, Paco; Lafuente, Maria Teresa; Alferez, Fernando (Frontiers in Plant Science, 2021)
Water stress is the most important environmental agent that contributes to the crop productivity and quality losses globally. In citrus, water stress is the main driver of the fruit peel disorders that impact the quality and market ability. An increasingly present post-harvest peel disorder is non-chilling peel pitting (NCPP). Non-chilling peel pitting is manifested as collapsed areas of flavedo randomly scattered on the fruit and its incidence increases due to abrupt increases in the environmental relative humidity (RH) during post-harvest fruit manipulation. In this study, we have used a custom-made cDNA microarray containing 44k unigenes from Citrus sinensis (L. Osbeck), covering for the first time the whole genome from this species, to study transcriptomic responses of mature citrus fruit to water stress. In the study, the global gene expression profiles of flavedo from Navelate oranges subjected to severe water stress are compared with those fruits subjected to rehydration stress provoked by changes in the RH during post-harvest, which enhances the development of NCPP. The study results show that NCPP is a complex physiological process that shares molecular responses with those from prolonged dehydration in fruit, but the damage associated with NCPP may be explained by unique features of rehydration stress at the molecular level, such as membrane disorganization, cell wall modification, and proteolysis.